No Allowances for Pessimism and Impossibility...: Or 2010 Çanakkale Regional Seminar on Public Libraries - İpek Tepecik (Türk Kütüphaneciliği)
Impressions from Çanakkale Regional Seminar on Public Libraries hosted by Çanakkale Public Library and held in cooperation with Turkish Librarians' Association, General Directorate of Libraries and Publications, Hacettepe University Department of Information and Document Management and Goethe Institute on December 3-5, 2010 are conveyed by İpek Tepecik, a sophomore student at the Department of Information and Document Management.